2018
DOI: 10.1017/s1930297500006628
|View full text |Cite
|
Sign up to set email alerts
|

Boosting intelligence analysts’ judgment accuracy: What works, what fails?

Abstract: A routine part of intelligence analysis is judging the probability of alternative hypotheses given available evidence. Intelligence organizations advise analysts to use intelligence-tradecraft methods such as Analysis of Competing Hypotheses (ACH) to improve judgment, but such methods have not been rigorously tested. We compared the evidence evaluation and judgment accuracy of a group of intelligence analysts who were recently trained in ACH and then used it on a probability judgment task to another group of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…Aggregation can benefit from transforming the original judgements, using some predefined function, and aggregating the transformed estimates. Various transformation methods have been proved to enhance the aggregated forecasting accuracy (Ariely et al 2000;Baron et al, 2014;Satopää et al, 2014;Mandel, Karvetski & Dhami, 2018;Turner, Steyvers, Merkle, Budescu & Wallsten, 2014). The quantile metric can also be used to evaluate the effectiveness of these transformations.…”
Section: Does Extremization Improve the Accuracy Of Aggregated Foreca...mentioning
confidence: 99%
“…Aggregation can benefit from transforming the original judgements, using some predefined function, and aggregating the transformed estimates. Various transformation methods have been proved to enhance the aggregated forecasting accuracy (Ariely et al 2000;Baron et al, 2014;Satopää et al, 2014;Mandel, Karvetski & Dhami, 2018;Turner, Steyvers, Merkle, Budescu & Wallsten, 2014). The quantile metric can also be used to evaluate the effectiveness of these transformations.…”
Section: Does Extremization Improve the Accuracy Of Aggregated Foreca...mentioning
confidence: 99%
“…Whitesmith (2019) found that ACH did not mitigate either confirmation bias or serial-position effects on the interpretation of evidence in reasoning about an intelligence analysis scenario (also see Lehner, Adelman, Cheikes & Brown, 2008). Mandel, Karvetski and Dhami (2018) found that intelligence analysts who were instructed to use ACH on a probabilistic hypothesis-testing task were less coherent and marginally less accurate in assigning probabilities to the hypotheses than analysts in a control group who were not instructed to use any SAT. Moreover, a subsequent examination of analysts' information use from the same experiment showed that analysts in the ACH condition were less likely to use relevant base-rate information than analysts in the control condition (Dhami, Belton & Mandel, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…Various transformation methods have been developed and proved to enhance the forecasting accuracy (Ariely et al, 2000;Baron et al, 2014;Satopää et al, 2014;Mandel, Karvetski & Dhami, 2018). Turner et al (2014) discussed the Lin-We use the terms judge, forecaster and expert interchangeably throughout the paper.…”
Section: Introductionmentioning
confidence: 99%